Ventriculo Peritoneal shunt catheter penetrating the Kidney: An unusual complication of shunt surgery - Teegala, Ramesh; Kanumury, Ramesh; Babu, Nagendra; Sai, BTS (Nepal Journal of Neuroscience, 2018)
Ventriculo Peritoneal (VP) shunt surgery is one of the commonly performed neurosurgical procedure in the management of hydrocephalus. Numerous complications related to this procedure are reported in the literature. Shunt malfunction related to the abdominal catheter is seen nearly 10-40% of cases. The catheter can perforate hollow viscous or solid organs. Among the solid organs, the kidney penetration was not reported in the English literature. We report an unusual case of VP shunt abdominal catheter migration in to kidney Ventriculo peritoneal shunt being one of the commonest procedures done by any neurosurgeon has many complications. Among them abdominal catheter complications like halo viscous perforation, abdominal wall perforation and extrusion through the natural orifices are considered to be rare. Solid organ perforations are very unusual and very limited numbers of these are reported.Nepal Journal of Neuroscience 15:27-28, 2018